PERFORMANCE OF COCONUT TIMBER UNDER FIELD AND SERVICE CONDITIONS - R.N. Palomar; V.K. Sulc (International Coconut Community Journal, 1990)
Approximately 3.4 million hectares of coconut plantation arc spread ail over the coconut producing provinces in the Philippines. Of these, 50% arc found in Mindanao, 21.l % in the Visayas and 28.9% in Luzon including the Southern Tagalog and Bicol regions (PCA Annual Report, 1986). It has been estimated that 30% of the area planted to coconut arc 60 years old and over. These coconut stands are considered unproductive and should be replanted with improved and high‑yielding coconut varieties.